Fatty Acid and Dietary Fibre Content of Walnut (Juglans regia L.) Varieties Grown in Turkey - Akca, Y.; Kara, H.; Yazicigil, Z.; Oztekin, Y.; Ozgen, M.; Sutyemez, M.; Kalyoncu, L. (Asian Journal of Chemistry, 2010)
Walnuts (Juglans regia L.), as part of healthy diet, contain multiple beneficial components such as unique fatty acid profile and high levels of Vitamin E, fibre and polyphenols. In this work, fatty acid profile and dietary fibre content of new walnut varieties grown in Turkey have been reported. For this purpose walnut samples were collected from 18 different varieties and genotypes grown in Turkey. Four international commercial varieties (`Heartley', `Pedro', `Chandler' and `Serr'), three Turkish commercial varieties (`Kaman', `Sebin', `Bilecik') and 11 new promising new genotypes were evaluated in terms of their fatty acid profile and total dietary fibre contents. Fatty acid composition was determined by gas chromatography and total dietary fibre determination was done by enzymatic-gravimetric procedure. Potential health benefits of newly selected Turkish walnut varieties showed promising results since 6 out of 14 newly selected varieties had more than 70% PUFA and all the new selections except one had more than 10% dietary fibre content.